2011
DOI: 10.5194/cp-7-117-2011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a dynamic background albedo scheme on Sahel/Sahara precipitation during the mid-Holocene

Abstract: Abstract.We have implemented a new albedo scheme that takes the dynamic behaviour of the surface below the canopy into account, into the land-surface scheme of the MPI-ESM. The standard (static) scheme calculates the seasonal canopy albedo as a function of leaf area index, whereas the background albedo is a gridbox constant derived from satellite measurements. The new (dynamic) scheme additionally models the background albedo as a slowly changing function of organic matter in the ground and of litter and stand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 46 publications
(60 reference statements)
4
88
0
Order By: Relevance
“…The evaluation of a 300-yr control simulation with ECHAM5/MPIOM already showed that the tropical sea surface temperature climatology is well simulated and that global-scale heat and freshwater-transport are in agreement with observations (Jungclaus et al, 2006). Furthermore, ECHAM5/MPIOM has been successfully applied to different paleoclimate states such as Mid-Holocene climate and transient Holocene climate simulations (Fischer and Jungclaus, 2010;Otto et al, 2009;Dallmeyer et al, 2010;Vamborg et al, 2011), Last Glacial Maximum simulations (Mikolajewicz, 2011;Arpe et al, 2011), Eemian climate simulations (Fischer and Jungclaus, 2010;Schurgers et al, 2006) and Eocene climate simulations (Heinemann et al, 2009).…”
Section: Ensemble Simulations With Echam/mpiommentioning
confidence: 85%
“…The evaluation of a 300-yr control simulation with ECHAM5/MPIOM already showed that the tropical sea surface temperature climatology is well simulated and that global-scale heat and freshwater-transport are in agreement with observations (Jungclaus et al, 2006). Furthermore, ECHAM5/MPIOM has been successfully applied to different paleoclimate states such as Mid-Holocene climate and transient Holocene climate simulations (Fischer and Jungclaus, 2010;Otto et al, 2009;Dallmeyer et al, 2010;Vamborg et al, 2011), Last Glacial Maximum simulations (Mikolajewicz, 2011;Arpe et al, 2011), Eemian climate simulations (Fischer and Jungclaus, 2010;Schurgers et al, 2006) and Eocene climate simulations (Heinemann et al, 2009).…”
Section: Ensemble Simulations With Echam/mpiommentioning
confidence: 85%
“…The integrated vegetation-soil feedback reinforced glacial cooling to some extent (Jiang, 2008). Further progress is shown in Vamborg et al (2011), in which the authors implemented a dynamic background albedo scheme within a comprehensive fully coupled GCM with vegetation dynamics (earth system model, ESM). In this model, the model additionally accounts for land surface albedo changes based on the calculation of carbon fluxes between terrestrial carbon pools (vegetation, litter and phytomass, and soil).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to vegetation dynamics, however, various studies also highlight the impact of physical soil characteristics on climate, as it represents another component of the land surface (Kutzbach et al, 1996;Doherty et al, 2000;Levis et al, 2004;Knorr and Schnitzler, 2006;Shellito and Sloan, 2006;Wanner et al, 2008;Brovkin et al, 2009;Micheels et al, 2009;Knorr et al, 2011;Krapp and Jungclaus, 2011;Vamborg et al, 2011;Lohmann et al, 2015). So far, model studies designed to examine soil dynamics have mainly focused on the sensitivity of individual physical soil characteristics and have therefore primarily addressed the monocausal impact of land albedo (Bonfils et al, 2001;Levis et al, 2004;Knorr and Schnitzler, 2006;Schurgers et al, 2007;Vamborg et al, 2011), soil texture, and maximum water-holding field capacity (Wang, 1999;Levis et al, 2004) on climate. Furthermore, Jiang (2008) investigated the role of physical soil characteristics (soil colour, soil texture) for the Last Glacial Maximum (LGM) by applying an atmosphere GCM, which was asynchronously coupled to a terrestrial biosphere model.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, climate in this region is affected by changes in land surface conditions (e.g. Xue and Shukla, 1993;Claussen, 1997;Zeng et al, 1999;Taylor et al, 2002;Koster et al, 2004;Vamborg et al, 2011;Patricola and Cook, 2010). Therefore, it is conceivable that changes in the type and intensity of anthropogenic land use and land cover change, perhaps caused by local or national conflict, will affect regional climate.…”
Section: Introductionmentioning
confidence: 99%